Pelatihan Bahasa Inggris Tips Sederhana Memahami Menggunakan Konteks Tenses Dalam Pembicaraan Sehari-Hari Untuk Murid Omah Amal Yogyakarta - surip Haryani (ABDIMAS Madani, 2023)
The application of English in daily communication is one of the ways to increase English proficiency. Anyone who learns English needs to apply daily speaking practice to increase English skills. The training was held on July 20 2022 through zoom meeting for participants from Omah Amal Yogyakarta. The service team provided training by providing examples of the easiest tenses table, explaining the easiest tricks to understand table tenses, providing examples of use in the simplest way to be applied, giving exercises and speaking applications by applying tenses tables and simulation examples from starting with lectures, simulations and practice. Assessment was given in the form speaking activities. The evaluation results show 85% of the participants understood and were able to apply the training materials well